Pengaruh Jenis Trichoderma spp. Terhadap Pertumbuhan, Hasil, dan Keberadaan Penyakit Tanaman Kacang Tanah (Arachis hypogaea L.) - KOMANG INTAN CAHYANI; I MADE SUDANA; GEDE WIJANA (Fakultas Pertanian Universitas Udayana, 2021)
The Effect of Trichoderma spp. on Growth, Yield, and Presence of the Diseases in Peanut (Arachis hypogaea L.). The consumption of peanuts is increasing together with increasing population, increasing nutrition, food diversification and increasing the capacity of the food and animal feed industry. However, the supply of peanuts in Indonesia is continues decline due to low soil nutrients and leaf rust attacks. The efforts can be made to increase peanut productions by applying Trichoderma spp. in peanut seeds. The purpose of this study was to determine the effect of Trichoderma spp. on the growth and yield of peanut plants, identifying the effect of Trichoderma spp. on the resistance of peanut plants to disease and know the best type of Trichoderma spp. for peanut plants. The design used in this study was a randomized block design (RCBD) with the treatment of a single factor type Tricoderma spp. which consists of 7 levels, namely: control, T. koningii, T. viride, T.asperellum, T. harzianum, T. ressei and T. asperellum Bedugul Bali. The treatment was repeated 4 times. The experimental results showed that the treatment of Trichoderma spp. significant until very significant effect on most of the observation variables. The best Trichoderma spp. is T. asperellum which has a very significant effect on the total number of pods (24.25 pods), weight of pods contained/plant (62.43 g), number of seeds/plant (62.75 seeds), and lowest leaf rust intensity (34,51%).